Memobilisasi Partisipasi Masyarakat dalam Kebijakan Pendidikan - Ali Imron (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
Mobilizing People Participation in Education Policy. Education policy is actually made and implemented to solve problems faced by people. Therefore, people involvement and participation should be encouraged in implementing the policy. Obviously, there are a number of ways to involve people to actively participate, but there are also many factors causing them unwilling to take part in the implementation of the policy. Societal involvement can be mobilized by knowing the supporting and the inhibiting factors.